MEDIA PEMBELAJARAN MATEMATIKA MATERI OPERASI HITUNG BILANGAN BULAT DI TINGKAT SD/MI - Suparni Suparni (DIRASATUL IBTIDAIYAH, 2021)
AbstractThe use of instructional media is very useful to complement students' understanding or understanding of the material being taught and the principle is to increase the effectiveness and smooth running of the learning process. The function of or benefits from the application of learning media in learning mathematics are: With the teaching aids, children will be morehappy to follow mathematics lessons, so that their interest in learning mathematics will increase. Children will be aroused, happy, interested and have a positive attitude towards maths lessons. By presenting abstract mathematical concepts in concrete form, students at lower levels will find it easier to understand and understand. Learning media can help the visibility of space, because they do not imagine geometric shapes, especially spatial geometric shapes, so that through pictures and real objects their discerning power will be helped so that they will be more successful in learning. What is around it, or between science and the surrounding environment and society. Abstract concepts that are presented in concrete form, namely in the form of a mathematical model can be the object of research and can also be used as a tool for researching new ideas and new relations Keywords: Media, Mathematics Learning, Counting Operations, Integer